Keratinous matrices for the assessment of drugs of abuse consumption: A correlation study between hair and nails. Issue 7 (7th February 2018) - Cappelle, Delphine; De Keukeleire, Steven; Neels, Hugo; Been, Frederic; De Doncker, Mireille; Dom, Geert; Crunelle, Cleo L.; Covaci, Adrian; van Nuijs, Alexander L.N.
Abstract: Keratinous matrices – hair and nails – accumulate substances over time and allow retrospective investigation of past consumption. Analysis of these matrices can provide information complementary to blood and urine analysis or can be used as standalone. So far, research has primarily focused on the detection of substances in hair, while studies in nails are scarce. In this study, we assessed concentrations of drugs of abuse and their metabolites in hair, fingernails, and toenails collected from the same individuals to evaluate differences and correlations between matrices. A total of 26 hair, 24 fingernail, and 18 toenail samples were collected. Samples were analysed by a validated liquid chromatography–tandem mass spectrometry method able to simultaneously detect the following compounds: amphetamine (AMP), methamphetamine, 3, 4‐methylenedioxymethamphetamine (MDMA), 3, 4‐methylenedioxyethylamphetamine, morphine (MOR), codeine (COD), 6‐monoacetylmorphine (6‐MAM), methadone (MTD), 2‐ethylidene‐1, 5‐dimethyl‐3, 3‐diphenylpyrrolidine (EDDP), cocaine (COC), benzoylecgonine (BE), and ecgonine methyl ester (EME). Strong positive correlations between hair, fingernails, and toenails were present for COC, BE, EME, AMP and MDMA. MOR, COD, 6‐MAM, MTD and EDDP showed positive trends. Concentrations were generally higher in nails compared to hair. Ratios between parent compounds and their metabolites were assessed for 6‐MAM/MOR, EDDP/MTD, BE/COC and EME/COC. Preliminary cut‐off concentrations for COC, BE, EME and AMP in fingernails and toenails were proposed. In light of these results, nails can be considered as a useful alternative to hair for monitoring of long‐term drug consumption. However, care should be taken regarding the variability in the accumulation of compounds between the matrices. Abstract : Concentrations of drugs of abuse and their metabolites are determined in hair, finger‐ and toenails collected from the same individuals to evaluate correlations between matrices. Positive correlations and relationships are found between hair, finger‐ and toenails. Concentrations are generally higher in nails compared to hair. Ratios between parent compounds and their metabolites are different between hair and nails indicating variances in accumulation. Nails can be considered as a useful alternative to hair for monitoring long‐term drug consumption.